Directional and Strain-Specific Interaction Between Lactobacillus plantarum and Staphylococcus aureus - Sandeep Kondakala; Sunghyun Yoon; Soumana Daddy Gaoh; Ohgew Kweon; Seong-Jae Kim; Mark E. Hart (Microorganisms)
The interaction between Lactobacillus plantarum and Staphylococcus aureus strains FRI-1169 and MN8, two original isolated strains from menstrual toxic shock syndrome (mTSS) cases, is a key focus for developing non-antibiotic strategies to control S. aureus-related infections. While the antagonistic effects of Lactobacilli species on S. aureus through mechanisms like organic acid and bacteriocin production are known, the molecular dynamics of these interactions remain underexplored. This study employs a proteomic approach to analyze the interactions between L. plantarum WCFS1 and S. aureus strains, FRI-1169 and MN8, during co-culture. We profiled differentially expressed proteins (DEPs) found in the spent media and cytosols of both bacteria, revealing distinct directional and strain-specific responses. The findings demonstrate that L. plantarum exerts a more pronounced effect on S. aureus, with more DEPs and upregulated proteins, while S. aureus showed fewer DEPs and more downregulated proteins. These strain-specific interactions highlight the complex metabolic and regulatory adjustments between these bacterial species. This research provides valuable insights into the molecular mechanisms of Lactobacillus-S. aureus antagonism and underscores the potential of proteomic analysis as a powerful tool for studying bacterial dynamics in co-culture systems.